Improving Banner Design Skill through the Application of Assignment Methods on Graphic Design Subject in Class X TKI IV SMK Negeri 2 Bandung - Surman, Ilham (Universitas Pendidikan Indonesia, 2022)
Graphic design is a form of visual communication that uses artistic text (typography) and images to convey information or messages. Graphic design has various techniques to produce works that are made, from manual to digital. Banner design is one of the prevalent products of graphic design and was made into one of the projects for class X TKI IV students. The objectives of this class action research (CAR) are 1) to observe student learning activities in designing banners through the method of presenting assignments, 2) to improve the skills of designing banners in class X TKI IV SMKN 2 Bandung, 3) to increase the average score of class X TKI students in Graphic Design subject. The methods used in this study are descriptive-quantitative which are divided into two cycles. The model used is collaborative learning between students and teachers. The result shows that there is an increase in student assignment completion in cycle 1 which is 59,46%, compared to cycle 2 which is 100% and an increase in student overall grades from 81,21 in cycle 1 to 87,83 in cycle 2.